Lipid-lowering effect of fluvastatin in relation to cytochrome P450 2C9 variant alleles frequently distributed in the Czech population - Buzková, Helena; Pechandová, Kristina; Danzig, Vilém; Vareka, Tomá; Perlik, Frantisek; Zak, Ales; Slanar, Ondrej (Medical science monitor, 2012)
BACKGROUND: CYP2C9*3 allele has been reported to correlate with increased plasma concentration of fluvastatin active form in healthy volunteers. We analyzed the correlation between the CYP2C9 genotype and cholesterol-lowering effect of fluvastatin in human hypercholesterolemic patients. MATERIAL/METHODS: The study was prospective, without any interventions to standard procedures of hypolipidemic treatment. CYP2C9 genotype was determined by PCR-RFLP assay in 87 patients on concomitant fluvastatin therapy, in 48 patients on monotherapy, and in a control group of 254 healthy volunteers of Czech nationality. Biochemical and clinical data were collected before the initiation of fluvastatin treatment and 12 weeks later. RESULTS: The frequency of CYP2C9 alleles did not differ significantly among groups of patients and volunteers. The most frequently observed allele was CYP2C9*2. Treatment with 80 mg of fluvastatin daily of 48 patients on monotherapy for 12 weeks resulted in mean low-density lipoprotein cholesterol (LDL-C) reduction by 25%, mean serum total cholesterol (TC) reduction by 21%, and mean triglyceride (TG) reduction by 28%. The CYP2C9*1/*3 genotype was associated with a decrease in LDL-C levels (by 40.0% for CYP2C9*1/*3, but only by 22.4% for CYP2C9*1/*1), and with the reduction of TC (by 28.6% in CYP2C9*1/*3 versus 20.2% in CYP2C9*1/*1). CONCLUSIONS: In hypercholesterolemic patients, LDL-C serum concentration was decreased more significantly in fluvastatin-treated subjects bearing the CYP2C9*1/*3 genotype compared to CYP2C9*1/*1 genotype. However, due to rare occurrence of some CYP genotypes, it was impossible to report a definitive positive genotype-fluvastatin effect association.
Keywords: dospělí; Indoles; cholesterol; Female; indoly; Fatty Acids, Monounsaturated; Genotype; hypercholesterolemie; Prevalence; Adult; Fluvastatin; ženské pohlaví; Československo; jednonukleotidový polymorfismus; anticholesteremika; fluvastatin; Gene Frequency; lidé; Polymorphism, Single Nucleotide; genotyp; studie případů a kontrol; Aged, 80 and over; frekvence genu; Cholesterol; prevalence; Anticholesteremic Agents; Hypercholesterolemia; Male; Case-Control Studies; Aged; Aryl Hydrocarbon Hydroxylases; cytochrom P450 CYP2C9; alely; kyseliny mastné mononenasycené; Alleles; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Czechoslovakia; Demography; Middle Aged; Cytochrome P-450 CYP2C9; aromatické hydroxylasy; demografie; Humans